Sodium channels as a new target for pain treatment - Chen, Rui; Liu, Yiran; Qian, Liu; Yi, Mingliang; Yin, Hong; Wang, Shun; Xiang, Bingbing (Frontiers in Pharmacology, 2025)
Voltage-gated sodium channels, especially the Nav1.7, Nav1.8, and Nav1.9 subtypes, play a crucial role in the transmission of pain signals. Nav1.7 is considered a threshold channel that regulates the generation of action potentials and is closely associated with various hereditary pain disorders. Nav1.8 primarily participates in inflammatory and neuropathic pain within the peripheral nervous system. Its characteristic of not involving the central nervous system makes it a potential target for non-addictive analgesics. Nav1.9 has shown significant involvement in cold pain sensing and small fiber neuropathy, although its mechanism of action is still under further investigation. Currently, despite promising results from preclinical studies, sodium channel inhibitors have not fully met expectations in clinical trials due to issues such as drug selectivity, dosing, and safety. The development of Nav1.7 and Nav1.8 inhibitors faces challenges such as drug intolerance, insufficient target occupancy, and off-target side effects. Future research may promote the development of non-opioid analgesics through combined inhibition strategies targeting multiple Nav subtypes, as well as improving drug selectivity and bioavailability. Overall, sodium channel inhibitors remain a key area of research in pain management, but their clinical application prospects still require further exploration.